2006
DOI: 10.1172/jci25901
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of noncalcemic, tissue-selective, nonsecosteroidal vitamin D receptor modulators

Abstract: Vitamin D receptor (VDR) ligands are therapeutic agents for the treatment of psoriasis, osteoporosis, and secondary hyperparathyroidism. VDR ligands also show immense potential as therapeutic agents for autoimmune diseases and cancers of skin, prostate, colon, and breast as well as leukemia. However, the major side effect of VDR ligands that limits their expanded use and clinical development is hypercalcemia that develops as a result of the action of these compounds mainly on intestine. In order to discover VD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 49 publications
1
89
0
1
Order By: Relevance
“…We recently reported that vitamin D 3 derivatives with adamantane or lactone ring side chain substituents are cell type-selective VDR modulators (10). Ma et al (9) reported that nonsecosteroidal compounds act as noncalcemic and tissueselective VDR ligands. These compounds are potent VDR agonists in keratinocytes, osteoblasts, and peripheral blood mononuclear cells but are less potent in intestinal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that vitamin D 3 derivatives with adamantane or lactone ring side chain substituents are cell type-selective VDR modulators (10). Ma et al (9) reported that nonsecosteroidal compounds act as noncalcemic and tissueselective VDR ligands. These compounds are potent VDR agonists in keratinocytes, osteoblasts, and peripheral blood mononuclear cells but are less potent in intestinal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Combined dosing of 1,25(OH) 2 D 3 with other drugs is one approach to overcome its adverse effects (7,8). The development of synthetic vitamin D analogs that retain VDR transactivation but have low calcemic activity provides another approach (9). With an improved understanding of the mechanisms of VDR signaling, the possibility of identifying VDR ligands with selective action is emerging (10).…”
mentioning
confidence: 99%
“…Additionally, we hypothesized that a synthetic compound could have other potential benefits to the elderly, such as improved neuromuscular function, anti-inflammatory/immunomodulation properties, inproved skin quality, and prevention of breast, colon, and prostate cancer. (13,(19)(20)(21)(22)(23)(24)(25)(26)(27) Therefore, compounds were evaluated for the ability to induce heterodimerization of VDR with RXR, resulting in the formation of a RXR-VDR heterodimer-ligand complex, which is a functional mediator of vitamin D action in cells. Alternatively, an RXR ligand will compete for RXR and disrupt RXR-VDR heterodimerization by driving the formation of the RXR-RXR homodimer.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the stably transfected ROS17/2.8 cell line (RG-15) containing Ocn-Luc has been described. (26) Confluent RG-15 cells maintained in DMEM/F-12 medium (3:1) containing 5% FBS and 300 mg/mL of G418 at 378C were trypsinized (0.25% trypsin) and plated into white opaque 96-well cell culture plates (25,000 cells per well). After 24 hours, cells (in DMEM/F-12 medium containing 2% FBS) were treated with the indicated concentrations of the compounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation